SCREENING OF ASPERGILLUS NIGER ISOLATED FROM SOIL FOR PECTINASE PRODUCTION - Madika, Abubakar; Asagha Eugene, Ulem; Bishir, Musa; Abdulkadir Sulaiman, Mamunu; Mohammed Hussaini, Ibrahim (FUDMA JOURNAL OF SCIENCES, 2020)
This study was conducted to screen for pectinase production by Aspergillus niger isolated from soil samples collected from three different locations within Ahmadu Bello University, Zaria, namely; botanical garden, refuse dump and sheep pen sites. A total of fifteen (15) soil samples were collected from different locations and used for isolation by a cultural method. Isolates suspected to be Aspergillus niger were further identified by microscopic examination of the lactophenol cotton blue stained-preparation and slide culture technique. The isolates were then screened in a pectin-containing medium for their pectinase activity. The isolates were further subjected to pectinase production using citrus pectin as the substrate under submerged fermentation conditions. Seven (7) isolates were confirmed to be Aspergillus niger with percentage occurrence of 60% each from sheep pen (SP) and refuse dumpsites (RD), and 20% from the botanical garden (BG). Aspergillus niger RD3 produced the highest zone of pectin hydrolysis (53 Â± 1.1 mm) while isolate RD5 produced the lowest (35 Â± 3.1 mm). Under submerged fermentation conditions, Aspergillus niger SP5 had the highest pectinase activity of 2.92 U/mL while isolate RD4 had the lowest pectinase activity of 1.29 U/mL. Aspergillus niger can be readily isolated from various soil types with the highest frequency in soils from sheep pen and refuse dumpsites. All the Aspergillus niger isolates demonstrated the potential for pectinase production. The study reveals the potential of various Aspergillus niger isolates from different soil in the production of pectinase.